The Influence of Influencer Marketing on Purchasing Decisions for Scientific Brand Products - Asyifa Rozen, Auliya; Suparman, S.; Riyanto, Sutisna; Dharmawan , Leonard; Khairunisa, Anggi Widia; Awalina, Salwa Putri (Golden Ratio of Data in Summary, 2025)
This study aims to analyze the influence of influencer marketing on purchasing decisions for Skintific products among audiences exposed to promotional content from influencer marketing. In the digital era, influencer marketing has become an effective strategy that utilizes social media platforms, especially Instagram and TikTok, to increase brand awareness and interaction with audiences. This research uses a quantitative approach, where data is collected through questionnaires distributed to consumers exposed to influencer marketing and analyzed using descriptive analysis methods. The results of the analysis show that influencer marketing has a relatively strong influence on purchasing decisions. In addition, factors show that the purchase channel and time of purchase are the two most influential factors in influencing purchasing decisions. This research provides a deeper understanding of how marketing can influence consumer purchasing decisions and the importance of choosing the right marketing strategy to increase product appeal.